2017
DOI: 10.1038/srep40091
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale synthesis of uniform hexagonal boron nitride films by plasma-enhanced atomic layer deposition

Abstract: Hexagonal boron nitride (h-BN) has been previously manufactured using mechanical exfoliation and chemical vapor deposition methods, which make the large-scale synthesis of uniform h-BN very challenging. In this study, we produced highly uniform and scalable h-BN films by plasma-enhanced atomic layer deposition, which were characterized by various techniques including atomic force microscopy, transmission electron microscopy, Raman spectroscopy, and X-ray diffraction. The film composition studied by X-ray photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 30 publications
1
40
0
Order By: Relevance
“…More recently, several new energy-enhanced processes of BN have been reported with the assistance of plasma, electrons, and hot wires. Park et al 71 demonstrated a new PEALD process using tris(ethylmethylamino) borane (TEMAB, B(N(CH 3 ) 2 ) 3 ) and plasma NH 3 ( P NH 3 ) in the range of 200 C-350 C. XRD confirmed the hexagonal structure of the as-deposited films, and HR-TEM revealed that the h-BN stacks were randomly distributed in the as-deposited films without any specific orientation. Creatively, Sprenger et al 72 developed an electron-enhanced ALD (EEALD) process using borazine (B 3 N 3 H 6 ) and electrons as precursors.…”
Section: -Bnhmentioning
confidence: 99%
“…More recently, several new energy-enhanced processes of BN have been reported with the assistance of plasma, electrons, and hot wires. Park et al 71 demonstrated a new PEALD process using tris(ethylmethylamino) borane (TEMAB, B(N(CH 3 ) 2 ) 3 ) and plasma NH 3 ( P NH 3 ) in the range of 200 C-350 C. XRD confirmed the hexagonal structure of the as-deposited films, and HR-TEM revealed that the h-BN stacks were randomly distributed in the as-deposited films without any specific orientation. Creatively, Sprenger et al 72 developed an electron-enhanced ALD (EEALD) process using borazine (B 3 N 3 H 6 ) and electrons as precursors.…”
Section: -Bnhmentioning
confidence: 99%
“…Other peaks, at 43° with a phase index of [100] and at 61°, were attributed to poor crystallinity and defective structure, as confirmed by HR-SEM and TEM micrographs. These defects were due to the nanometer size of the whiskers [38] resulting in a turbostratic morphology, a type of shape found among hexagonal and amorphous materials [47,48].…”
Section: Resultsmentioning
confidence: 99%
“…Cubic BN is an important material because of its properties such as super hardness 75 GPa [6][7][8] high thermal stability for temperatures up to 2700°C, thermal conductivities of about 13 W/m K and low dielectric constant [9][10][11][12]. It is a better semiconductor as compared to diamond and other commonly used semiconductors such as Si and GaN including, wide indirect band gap of 6.5 eV, can be doped as a shallow p-type semiconductor with Be and Mg and as an n-type with Si and Zn [13,14]. It is inert with regards to ferrous materials even at high temperatures while diamond forms iron carbide at about 600°C [3,5].These properties have motivated the use of c-BN in numerous industrial, chemical and electrical applications [15][16][17][18].…”
Section: Accepted Manuscriptmentioning
confidence: 99%